2018
DOI: 10.1186/s12940-018-0430-x
|View full text |Cite
|
Sign up to set email alerts
|

Associations of greenness, greyness and air pollution exposure with children’s health: a cross-sectional study in Southern Italy

Abstract: BackgroundDue to the complex interplay among different urban-related exposures, a comprehensive approach is advisable to estimate the health effects. We simultaneously assessed the effect of “green”, “grey” and air pollution exposure on respiratory/allergic conditions and general symptoms in schoolchildren.MethodsThis study involved 219 schoolchildren (8–10 years) of the Municipality of Palermo, Italy. Data were collected through questionnaires self-administered by parents and children. Exposures to greenness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 45 publications
2
30
1
Order By: Relevance
“…We failed to explain any association of local differences in air pollution from the traffic with either symptoms or COPD, as both CAT, mMRT scores, and COPD prevalence were similar in those living in the first, second, third or even fifth row of houses from the major road. Outdoor air pollution in studies elsewhere consistently showed greater likelihood of respiratory symptoms in both children and adults [24][25][26][27] and COPD. [8][9][10] We hypothesize, that the basic air pollution level in Almaty is so high, that a distance of 50 to 100 meters from a major road cannot play a role in worsening the symptoms.…”
Section: Figurementioning
confidence: 90%
“…We failed to explain any association of local differences in air pollution from the traffic with either symptoms or COPD, as both CAT, mMRT scores, and COPD prevalence were similar in those living in the first, second, third or even fifth row of houses from the major road. Outdoor air pollution in studies elsewhere consistently showed greater likelihood of respiratory symptoms in both children and adults [24][25][26][27] and COPD. [8][9][10] We hypothesize, that the basic air pollution level in Almaty is so high, that a distance of 50 to 100 meters from a major road cannot play a role in worsening the symptoms.…”
Section: Figurementioning
confidence: 90%
“…Six studies were performed on birth cohorts; 18-23 6 had a cross-sectional design; 18,24-28 1 was an intervention study; 29 and 1 was a case-control study. 30 Twelve studies involved children of age 12 years, [19][20][21][22][23][24][25][26][27][29][30][31] and only two included children and adolescents. 18,28 Most of the studies were conducted in Europe, 19,23,24,27,30 2 in Australia, 21,25,26,28 4 in North America, 18,31 1 in Asia, 29 and 1 based on data from Swedish, Dutch, German, Australian, and Canadian birth cohorts.…”
Section: Resultsmentioning
confidence: 99%
“…There were 5 different methods for assessing greenness exposure. The Normalized Difference Vegetation Index (NDVI), used by 10 articles [19][20][21][22][23][24][26][27][28]30 , is a validated tool assessing vegetation cover in order to quantify the amount of vegetation derived from publicly available satellite images. NDVI is based on land surface reflectance, ranging from 0 to 1, where 0 means no vegetation and values close to 1 (0.8-0.9) indicate the highest possible density of green leaves.…”
Section: Exposure Assessmentmentioning
confidence: 99%
“…There is evidence that air pollution can exacerbate existing respiratory health problems [1,9]; however, whether air pollution may also cause respiratory disease is less certain, since previous studies show conflicting results [10] with limitations on exposure assessment and on the ability to control for individual potential confounders [11]. Recently, the quality of the exposure assessment has been improved, using exposure models that combine data from air quality monitoring stations and satellite data, along with territorial data (e.g., land use) and meteorological parameters [12,13]. These new techniques allow investigating long-term health effects through individual and objective measures of air pollutants exposure.…”
Section: Introductionmentioning
confidence: 99%